A Implementasi Program Pertukaran Mahasiswa Merdeka dalam Peningkatan Sikap Moderasi Beragama - Nurdiansyah, Ilham; Munawaroh, Nenden; Tutun Usman, Asep (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
This study aims to examine the application of the Nusantara Module course on the attitude of religious moderation in PAI students at Garut University. The approach in this research is descriptive qualitative with data collection and processing techniques by means of data triangulation. The results showed that the implementation of the Nusantara Module in the Independent Student Exchange Program was effective in shaping attitudes of religious moderation. In this course, students interact directly with each other who have different religious, cultural, racial and linguistic backgrounds in participating in module activities in the form of diversity, reflection, inspiration and social contribution. This module develops several main indicators, such as national commitment, tolerance, non-violence, and an accommodating attitude towards cultural values. Changes in student attitudes not only reflect a deeper insight into cultural diversity in Indonesia, but also contribute to strengthening moderation values among the community. These findings are expected to be the basis for curriculum design that is more inclusive and responsive to the social and religious dynamics in Indonesia.